Beidelita de la mina Dos Amigos, Los Menucos, prov. de Río Negro, Argentina - Maiza, Pedro (1996)
The presence of beidellite developed in veins from the core of the fluorite vein Dos Amigos (Prov. de Rio Negro) is cited. It was studied bv means of XRD, optical microscopy, SEM, TG, DTA, IR and Chemical analysis. The beidellite is associated to fluorite and quartz, with subordinated kaolinite. It has a good crystallinity. It is considered to have been formed in the latest stage of mineralization, from the fluids that give rise the fluorite vein.